Systematic Literature Review (SLR): Kompetensi Sumber Daya Insani Bagi Perkembangan Perbankan Syariah Di Indonesia - Luluk Latifah; Iskandar Ritonga (Al Maal: Journal of Islamic Economics and Banking, 2020)
Human resources have an increasingly important role in achieving the objectives of a governmental, private, corporate organization, including sharia banking. This study aims to find out how the development of human resource competencies in Islamic banking in Indonesia is seen from the theoretical and practical order, and how the solution is solved. With the paradigm approach of Systematic Literature Review in journals that have been publicized from 2016 to 2020, the results show that the low level of competence of human resources in Islamic banking in Indonesia both at the theoretical and practical level. sharia. in Indonesia. The solutions provided are: 1) Recruitment, selection and placement of human resources properly adjusted to their skills 2) Pay close attention when recruiting DPS (Sharia Supervisory Board) must really be competent both in terms of sharia and finance. 3) Increasing the role of tertiary institutions especially Islamic tertiary institutions to provide competent human resources by taking into account the existing integrity of sharia banking and being advised by the government as policy maker. 4) Increase the competence of human resources by increasing theoretical and practical aspects. 5) The ability of human resources in modifying Islamic sharia products and understanding of sharia contracts.